Design and implementation of an efficient security protocol for wireless vehicle communications - Chen, Hongmei. (2011)
Nowadays the vehicular ad hoc network (VANET) communications enables a variety of applications for safety, traffic efficiency, driver assistance as well as infotainment. In a VANET, network topology changes constantly as vehicles move in and out of wireless range quickly.